The Seed industry in Pakistan: Regulation, politics, and entrepreneurship - Rana, Muhammad Ahsan (International Food Policy Research Institute, 2014)
Seed provision in Pakistan is experiencing tension as private entrepreneurs have been challenging the boundaries of the country’s ar-chaic regulatory structure. All key aspects of the system – licensing of seed producers, variety release procedures, access to public germplasm, quality control, intellectual property rights, and import and export –are governed by laws and regulations framed decades ago for a system then dominated by public sector enterprises. Since the early 1980s, the private seed business has grown but govern-ance has failed to keep pace. The failure of regulatory frameworks to evolve has constrained business activity, at least through official channels. Most actors, including some public sector enterprises, have on occasion found answers in the informal sector, which now mediates a substantial portion of the trade.